Analogías entre la curva de Allen y el ciclo de Carnot - Freyre, Lauce Rubén (1977)
Two sucessive generalizations of Allen's curve are suggested by the author; the first one for a sum of cohortes, the population, and the other for a sum of populations, the community or a part of it. Both of them are proposed for the study of energetic relations in an ecosystem as well as for the description of populations displacements among the communities in function of the ambient changes during an annual cycle.